An integrative model for measuring graduates' employability skills—A study in China - Wenping Su; Miao Zhang; Tahir Nisar (Cogent Business & Management, 2015)
Employability is a key issue in graduates' job-hunting, but little research has been done on that of the graduates in Chinese universities. These universities have been experiencing a decline in their graduate employment since the past decade. This paper attempts to tackle this issue. It reviews the relevant research on employability and develops a research-based theoretical framework to evaluate and analyze the graduates' employability in China. It adopts multiple approaches to establish the skills that will enhance university students' employability. Investigating around 100 employers and 200 undergraduates from the universities in Beijing, the paper explores the characteristics of and factors influencing the graduates' employability. Subsequently, it proposes a qualitative model to measure graduates' employability. Based on the findings, it discusses the theoretical and practical implications and provides advice for Chinese graduates to improve their employability.
Keywords: 650